Strategi Penerapan Kedisiplinan Guru Pendidikan Agama Kristen dalam Pembelajaran dan Bermain Anak Usia 3-5 Tahun - Wiranto Wiranto; Sandra Tapihala (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The purpose of learning discipline is to teach behavior. When teaching kids to give up, the key is asking them to do the right thing for the right reasons. What is initially external because of pressure from parents or the external environment, but then becomes something internal and integrates with the child's personality, then it is called discipline. Children learn to play while playing. It is too easy for children to carry out the learning process in a teacher's own way, inseparable from school or homeschooling. This is the world of children, the world of exciting games. The child's world is basically a world of play, especially at an early age.